Pneumonia in patients with chronic kidney disease V D stage: pathogenetic aspects of complex therapy and outcomes - I. Shifris; L. Korol; O. Magas; E. Krasiuk; I. Dudar (Ukrainian Journal of Nephrology and Dialysis, 2019)
Abstract.The aim of our study was to increase the effectiveness of treatment of comorbid pneumonia in patients with CKD VD stage.Materials and Methods. 73 patients with CKD VD st. (59 on HD and 14 on PD) with mild to moderate comorbid pneumonia who received renal replacement therapy (RRT) during 2013-2016 were included in the observational prospective open-label randomized trial. Patients were randomized into two groups: group 1 (n = 42) included patients who in addition to the conventional therapy of pneumonia received medication «Lipin» as a complex therapy; group 2 included patients (n = 31) who received only basic (traditional) therapy. The groups were representative by the main demographic, social and clinical-laboratory findings, severity of pneumonia, duration and modality of RRT. The primary endpoints were death from any cause and episodes of rehospitalization. The overall assessment of the clinical efficacy of the therapy was based on a comparison of the duration of hospitalization, antibiotic therapy, intoxication syndrome, and regression of X-ray changes.Survival in observation groups was determined by the Kaplan-Meier method. Analyzed cases were included to October 31, 2018.The markers of oxidative stress (OS) were determined in 29 patients of group 1 and 14 patients of group 2 before treatment and after 14 days while treatment of  pneumonia was started.Results. The analysis demonstrated that during a 1-year period a 17 (25,76%) episodes of rehospitalization were recorded: 11 causes (35.5%) in group 1 and 6 (14.3%) in group 2 (χ² = 4.486, p = 0.035). In total, 29 deaths were recorded during the study period: 10 (23.8%) cases in group 1, and 19 (61.3%) - in group 2 (χ² = 8.957, p = 0.003, RR - 2.574, 95% CI: 1.400-4.733). The three- and five-year cumulative survival rates were 83% vs. 21% and 59% vs. 21%, in the group 1 and group 2, respectively (p = 0.00003). It was stated that the duration of hospitalization, antibiotic therapy, intoxication syndrome and X-ray regression were significantly lower in group 1 compared with group 2 (p <0.05). The comparative analysis of dynamics in the groups shows that increasing the treatment effectiveness at complex therapy background accompanied by a significant positive dynamics of OS markers (p <0,05).Conclusions Thus, the results of this study demonstrated the effectiveness of complex method of pneumonia treatment in patients with CKD stage 5D including Lipin medication compared traditional therapy. There is a significant difference in patient survival depending on the proposed and generally accepted treatment.